In vitro antihepatocellular carcinoma activity of secondary metabolites of Centaurea kilaea Boiss - ŞEN, ALİ; ŞENER, AZİZE; BİTİŞ, LEYLA; ŞEKERLER, TURGUT (MARMARA UNIV, 2020)
The aim of this study was to investigate in vitro cytotoxic effects of previously isolated compounds (taraxasterol, salvigenin, 3'-O-methyleupatorin, oleanolic acid, jaceosidin and pectolinarigenin) from Centaurea kilaea chloroform extract on hepatocellular carcinoma cell lines, HepG2 and Hep3B, as well as to evaluate the effect on the normal cell line, NIH3T3. In vitro antihepatocellular carcinoma activity of compounds was assessed by MTT method. All compounds except pectolinarigenin caused more inhibition on HepG2 rather than Hep3B. Among these compounds, it was found that Jaseosidin had the highest anticancer activity with IC50 values of 137.66 mu g/mL and 147.66 mu g/mL on the HepG2 and Hep3B cell lines, respectively. 3'-O- methyleupatorin showed the second highest cytotoxicity with IC50 values of 151.98 mu g/mL and 159.24 mu g/mL against the HepG2 and Hep3B cell lines, respectively. The results indicated that Jaseosidin and 3'-O-methyleupatorin, had the best antiproliferative activity against hepatocellular carcinoma cell lines. Also, according to our best knowledge, this study is first report on antihepatocellular carcinoma activity of Jaseosidin and 3'-O-methyleupatorin.
Keywords: Centaurea kilaea; anticancer activity; hepatocellular carcinoma; jaceosidin; 3 '-O-methyleupatorin; BIOACTIVITY-GUIDED ISOLATION; ANTIPROLIFERATIVE ACTIVITY; CONSTITUENTS; GUAIANOLIDE; EXTRACT